Vinylimidazole‐based asymmetric ion pair comonomers: Synthesis, polymerization studies and formation of ionically crosslinked PMMA. Issue 15 (15th May 2013) - Jana, Satyasankar; Vasantha, Vivek Arjunan; Stubbs, Ludger Paul; Parthiban, Anbanandam; Vancso, Julius G.
ABSTRACT Vinylimidazole‐based asymmetric ion pair comonomers (IPCs) which are free from nonpolymerizable counter ions have been synthesized, characterized and polymerized by free radical polymerization (FRP), atom transfer radical polymerization (ATRP), and reversible addition‐fragmentation chain transfer (RAFT) mediated polymerizations in solution and by dispersion polymerization in water. The asymmetric nature of IPCs is due to the fact that cationic component of these IPCs is derived from vinylimidazole (VIm) and anionic component is derived from either styrenesulfonate (SS) or 2‐acrylamido‐2‐methyl‐1‐propanesulfonate. Although under ATRP, conversions are either very low or negligible, FRP and RAFT produces polymers with high to moderate monomer conversions but with different solubility characteristics. This investigation provides insight to the polymerization behavior of each component of the asymmetric IPCs and also its effects on composition and solubility characteristics of the resulting polymers. The IPCs studied here are high temperature ionic liquid and thus the polymers synthesized from these IPCs are highly ionic in nature and possess very strong intermolecular interactions which makes some of these IPC based polymers completely insoluble in organic and aqueous solvents. This highly ionic interaction is exploited to synthesize ionically crosslinked PMMA. MMA on copolymerization with 5–6 mol % of IPC yielded copolymer which is insoluble in common organic solvents like THF, DMF, etc., unlike homo PMMA. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 3260–3273